KETERTARIKAN REMAJA TERHADAP KOMUNITAS PUNK - Mukhlis Mukhlis; Alma Yulianti; Ina Sakinah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
This research aims to study the teenagers interest toward punk community. Having qualitative method with interview, observation, and documentation, this research involved six respondents from the oi and skinhead community. Result shows internal and external factors in which internal factors are need for freedom, need for existence, identity crisis and influencing each others. Meanwhile external factors are unharmonious relationship with their family, peer influence and interest toward rock punk musi and punk make up.